Entrepreneurial small business - Katz, Jerome A. (McGraw - Hill, 2007)
Describing companies whose goals are personal independence with financial security, this book talks about traditional beliefs and models in small business. It presents the advanced findings and best practices from academic and consulting arenas. It focuses on the challenges facing entrepreneurs.